Good Governance In Structure Belantik Raya People's Market In Siak District - Nurman; Zainal; Yudha Rajasa (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2021)
The guidance carried out by the Department of Trade and Industry of Siak Regency on the Belantik Market which is included in the Indonesian National Standard (SNI) People's Market is one of the government's efforts to realize good governance. This study aims to determine and analyze the application of good governance in the arrangement of the Belantik Raya People's Market in Siak Regency. This research method is descriptive qualitative. Data analysis technique using triangulation technique. The results of this study explain that the implementation of good governance in the arrangement of the Belantik Raya People's Market in Siak Regency has been running for 2 (two) years in accordance with the rules that apply as an SNI Market. If it is associated with the theory of good governance, according to Sedarmayanti, the indicators are: Accountability, Transparency, Openness, Legal Certainty/Rule of Law that the application of the Belantik Raya People's SNI in Siak Regency not only benefits traders, but also benefits consumers. This is because SNI Pasar Rakyat emphasizes the factors of cleanliness, health, safety and comfort. The market manager is currently monitoring all the requirements that must be met by Belantik Raya Market as an SNI People's Market which is under the auspices of the Siak Regency Trade and Industry Office. it must be improved as a whole, this is of course the need for coordination and communication between traders and the government, because to maintain this SNI is the cooperation of all of us in Siak Regency.